Determinación del perfil renal, proteínas totales y su relación con la microalbuminuria en pacientes diabéticos como ayuda diagnóstica en la prevención de nefropatías - Rodríguez Carrión, Andrea Karolina (2014)
Diabetes is a metabolic disorder with a high prevalence in our population and actually presents statistical values of high mortality. One of the most severe complications is diabetic nephropathy, hence the importance of the development of this research that having finality to determine the renal profile, total protein and view their relationship with microalbuminuria in diabetic patients as a diagnostic help in the prevention of nephropathy applied to diabetic patients attending the Health Subcentre Obrapia, Chontacruz and Miraflores in the period February - March 2014. The detection of high values of both the renal profile, and total blood serum protein and microalbuminuria in urine of diabetic patients, are helpful because they give us an indication of how the kidney is functioning and thereby preventing the development of diabetic nephropathy can be achieved. The study was conducted in 67 diabetic patients in which 1.49% corresponding to 1 diabetic patient has Urea increased values, which corresponds to 8.95% of the 6 diabetic patients have increased in creatinine values and corresponding to 5.97% of the 4 diabetic patients have elevated levels of uric acid. In the proof of the Total Protein we have to 8.95% representing of the 6 diabetic patients have high values of this parameter with respect to microalbuminuria 11.94% for the 8 patients studied presented values increased in this test. That is why the obtained results from the study show the recommended run a Preventive Health Program for diabetic patients in order to influence health policies to strengthen prevention of chronic degenerative diseases, preferably with emphasis on changes in lifestyle also conducting frequent talks is recommended especially on the risk involved in diabetes and complications from not keep appropriate control of the disease, the routine monitoring of patients with these laboratory tests is vital to know the health status of the patients and so keep inside normal ranges in order to prevent future diabetic patient suffering diabetic nephropathy. KEYWORDS Diabetes Mellitus, Diabetic nephropathy; renal profile; total protein, Microalbuminuria.